2018
DOI: 10.1002/pst.1890
|View full text |Cite
|
Sign up to set email alerts
|

Bayesian dose‐finding phase I trial design incorporating pharmacokinetic assessment in the field of oncology

Abstract: The main purpose of a phase I dose-finding study in the field of oncology is to evaluate toxicity and pharmacokinetic (PK) data and to estimate the optimal dose (OD) for subsequent clinical trials. From a pharmacological perspective, PK information is considered as an appropriate indicator for evaluating the degree of drug intervention in humans. Dose proportionality is typically assessed to investigate the PK properties of a drug. If we rely solely on the dose-exposure relationship, then when this relationshi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 21 publications
0
17
0
Order By: Relevance
“…Although Rolling 6 is our recommendation for a Phase II safety run-in that requires pharmacokinetic assessment, for standard Phase I trials methods have been proposed to incorporate pharmacokinetic assessment. 28…”
Section: Discussionmentioning
confidence: 99%
“…Although Rolling 6 is our recommendation for a Phase II safety run-in that requires pharmacokinetic assessment, for standard Phase I trials methods have been proposed to incorporate pharmacokinetic assessment. 28…”
Section: Discussionmentioning
confidence: 99%
“…It was found that, for the studied scenarios, trial efficiency (as measured by the number of observed dose‐limiting toxicities or the probability of correct MTD selection) is not improved, but the estimation of the dose–toxicity curve may be better compared to the designs that do not utilize PK data. Another recent paper 50 proposed a Bayesian dose finding design using dose‐exposure data in the escalation rule and found that it may improve the probability of correct dose selection. An important and potentially useful consideration is the assessment of distributed designs (evaluating a range of doses) versus concentrated design (testing only placebo and the maximum dose).…”
Section: Integration Of Fieldsmentioning
confidence: 99%
“…However, it has been shown by Ursino et al [ 23 ] in a simulation study that none of these approaches has a significant edge over previous methods. Ursino et al [ 23 ] and more recently Takeda et al [ 24 ] have proposed more elaborate methods with attempts of a better integration of the PK. However in both manuscripts simple estimation of the drug exposure were used while the between patients variability was not appropriately characterized.…”
Section: Introductionmentioning
confidence: 99%
“…The potential variability in bioavailability or of absorption in case of flip-flop kinetics [ 25 , 26 ] are ignored. Takeda et al [ 24 ] considered simplified non-linear kinetics not reflecting what is observed in case of saturated absorption for instance or for target mediated drug disposition antibody. Furthermore, the authors used inflated measurement errors in lieu of between patients variability.…”
Section: Introductionmentioning
confidence: 99%